2019
DOI: 10.1115/1.4043166
|View full text |Cite
|
Sign up to set email alerts
|

A Systematical Study of the Influence of Blade Number on the Performance of a Side Channel Pump

Abstract: For side channel machines, distinction is made between side channel pumps and peripheral pumps. The blade number of side channel machines has a large influence on the performance of the pump. This is known from several experimental studies. For industrial side channel pumps, the blade number is between 20 and 26, whereas for industrial peripheral pumps, the blade number is much larger (between 36 and 90). In this paper, the influence of the blade number on the performance and the inner flow phenomena of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Geometric recommendations were put forward to reducing vibration and increasing component life through the reductions in pressure pulsations. Fleder and Böhle [20] investigated the effect of blade number on the flow characteristics and performance of different pumps by CFD simulations and experiments. It is shown that the number of blades has a significant influence on the circulation velocity and flow angles between blades and side channel.…”
Section: Introductionmentioning
confidence: 99%
“…Geometric recommendations were put forward to reducing vibration and increasing component life through the reductions in pressure pulsations. Fleder and Böhle [20] investigated the effect of blade number on the flow characteristics and performance of different pumps by CFD simulations and experiments. It is shown that the number of blades has a significant influence on the circulation velocity and flow angles between blades and side channel.…”
Section: Introductionmentioning
confidence: 99%
“…While vortex pumps provide high head, the internal vortices cause significant energy dissipation [14,15], leading to generally low efficiency values for these pumps. Therefore, controlling energy dissipation within vortex pumps to enhance their performance has been a significant research focus for many scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, energy losses are inevitable leading to its low efficiency usually less than 50%. Authors notably [29][30][31][32][33][34] have provided exhaustive studies on the complex flow patterns and performance optimization of side channel pumps. Fleder and Böhle 35 numerically and experimentally studied the influence of the blade shape on the performance of a side channel pump.…”
Section: Introductionmentioning
confidence: 99%